Thermodynamic simulations of rankine, trilateral and supercritical cycles for hot water and exhaust gas heat recovery - Hiroshi KANNO (The Japan Society of Mechanical Engineers, 2014)
Trilateral cycle is one of the heat cycles for waste heat recovery system. In the heat exchange process of the trilateral cycle, pressurized working fluid is kept as a single liquid phase. Therefore, temperature-profile matching between the heat source and the working fluid should be improved, and exergy loss can be minimized. In the present study, thermodynamic performances of Rankine, trilateral and supercritical cycles are assessed. In the cycle simulation, maximum pressures of these three cycles are optimized to give the highest exergy efficiency. Cycle performance criteria are sink-temperature-based exergy efficiency, isentropic expansion ratio and maximum pressure. Exhaust gas (400℃) and hot water (80℃) are assumed for the heat sources. Simulation results show that the sink-temperature-based exergy efficiency of trilateral cycle is 78 %, which is 1.36 times larger than that of Rankine cycle for the hot water case. For the exhaust gas case, water is the optimal working fluid for the trilateral cycle, and the sink-temperature-based exergy efficiency is 80 %. Especially in the trilateral cycle, the optimum expansion ratio shows large variation depending on the working fluids and working conditions. Thus, a reciprocating expander should be suitable from the view point of adaptability to various working conditions. In the present study, the effect of volumetric expansion ratio with reciprocating expander is also investigated. Simulation results show that the volumetric expansion ratio of 100 or even higher is needed to reduce the expander loss.